Implement Guidance model for ISO 11783 standard. Issue 16 (2016) - Oksanen, Timo; Backman, Juha
Abstract: Automatic guidance systems for agricultural tractors are steering only the tractor, not the implement connected to the tractor. In a long trailer type implement, the deviation from the path may become remarkable under lateral forces causing navigation error. The implement steering combined with tractor steering would improve the accuracy remarkably, but there is no standard yet for multi-brand systems to operate as plug-and-play. Current systems are either two independent guidance systems, one for tractor and another one for implement, or the combined solution is provided from the same vendor. In both cases, the implement steering mechanism is usually retrofitted. In this paper, we present a model based on abstract implement to be included in ISO 11783 standard series. This model allows not only the data exchange model between the guidance system and the implement, but also makes the development of a guidance system easier. By using the abstract implement model, the guidance system may rely on a common kinematic model that is suitable for any implement with steering capabilities.